2019
DOI: 10.1103/physrevb.99.235123
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints of the conformal anomaly in the thermoelectric transport in Dirac and Weyl semimetals

Abstract: A quantum anomaly arises when a symmetry of the classical action can not survive quantization. The physical consequences of having quantum anomalies were first explored in the construction of quantum field theory to describe elementary particles and played an important role in grand unification and string theory. Nowadays, the interest on anomalies and anomaly related transport has shifted to emergent condensed matter systems which support low energy descriptions akin to their QFT partners. Dirac and Weyl semi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
(55 reference statements)
1
24
0
Order By: Relevance
“…In a recent publication [29], it was shown that the conformal anomaly [30], related to metric deformations, gives rise to a special contribution to the Nernst signal which remains finite at zero temperature and chemical potential, a very unusual property. This result was later confirmed with a more standard Kubo calculation in [31]. In this work we analyze the validity of the phenomenological thermoelectric relations in Dirac and Weyl semimetals in the conformal limit (zero temperature and chemical potential).…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…In a recent publication [29], it was shown that the conformal anomaly [30], related to metric deformations, gives rise to a special contribution to the Nernst signal which remains finite at zero temperature and chemical potential, a very unusual property. This result was later confirmed with a more standard Kubo calculation in [31]. In this work we analyze the validity of the phenomenological thermoelectric relations in Dirac and Weyl semimetals in the conformal limit (zero temperature and chemical potential).…”
Section: Introductionsupporting
confidence: 62%
“…A non-zero thermoelectric coefficient was predicted at zero temperature and chemical potential where the theory is scale invariant at the classical level. A Kubo formula calculation of the thermoelectric coefficient extended the calculation to finite temperature and chemical potential and gave the same result in the conformal limit [31].…”
Section: The Action Associated To This Hamiltonian In the Presence Ofmentioning
confidence: 69%
See 3 more Smart Citations